What drives carbon emissions in the Yellow River Basin: new insights from multi-scale analysis based on nighttime light data - Ma, Mingjuan; Gao, Wenwen; Li, Qiang (Frontiers in Environmental Science, 2025)
Developing targeted carbon emissions reduction strategies of the Yellow River Basin (YRB) is essential for achieving sustainable development. At present, nighttime light data provide favorable conditions for studying carbon emissions of large-scale and long-time series. Utilizing nighttime light and statistical data from 2000 to 2022, the spatial-temporal variations of carbon emissions at multi-scale in the YRB are estimated and analyzed. Furthermore, the spatial spillover effects and influencing factors of carbon emissions in the YRB are explored combining Exploratory Spatial Data Analysis (ESDA) and spatial econometric model. The study aims to provide crucial insights for formulating effective carbon emission mitigation strategies in the YRB. Our findings delineate three distinct phases of provincial carbon emissions in the YRB from 2000 to 2022, each marked by unique stages and a converging trend. Urban carbon emissions present distinct spatial distribution characterized by “lower reach > middle reach > upper reach.” Spatial correlation test highlights significant spatial clustering characteristics and spillover effects of carbon emissions. Further decomposition of spatial effects reveals that carbon emissions are influenced by the synergistic interactions of various resource elements. Factors such as economic growth, population density, industrial structure, energy consumption structure, technological progress, and foreign direct investment exert complex interactive effects on carbon emissions.